Understanding drivers of human tolerance to gray wolves and brown bears as a strategy to improve landholder–carnivore coexistence. Issue 3 (18th September 2020) - Marino, Filippo; Kansky, Ruth; Shivji, Irene; Di Croce, Antonio; Ciucci, Paolo; Knight, Andrew T.
Abstract: Despite recent recovery of large carnivores throughout Europe such as the brown bear ( Ursus arctos ) and the gray wolf ( Canis lupus ), some of their populations are still threatened and their viability depends on human tolerance to share mixed landscapes. We investigated the drivers of landholders' tolerance in Abruzzo (Italy), a region with a long history of cohabitation, by applying the Wildlife Tolerance Model (WTM) (Kansky et al., 2016, Biological Conservation, 201, 137–145). Using structural equation modeling we assessed relationships between WTM variables. This framework hypothesizes that exposure to a species and experiences with a species drive perceptions of benefits and costs, and ultimately tolerance. We then sought to understand similarities and differences in tolerance drivers between the two species and across two areas that differed in the duration of human–carnivore cohabitation. Results showed both similarities and differences in drivers between species and areas, resulting in seven management proposals to foster tolerance. Increasing intangible benefits and positive experiences were two strategies that were similar for both species and areas, while five strategies differed across species and areas. Our methodological approach can be applied in other landscapes with other species to determine the extent to which multispecies management across landscapes is possible. Abstract : Given the reliance of large carnivores' viability on human tolerance, we investigated drivers of landholders' tolerance toward the gray wolf and the brown bear in the cultural landscape of Abruzzo (Italy) by using a theoretical framework, the Wildlife Tolerance Model. We identified similarities and differences in tolerance drivers between the two species and across two areas to inform conservation management, and we elaborated seven management proposals to foster tolerance, such as increasing intangible costs and positive experiences. Our methodological approach can be applied in other landscapes with other species to determine the extent to which multispecies management across landscapes is possible.